Risky Sexual Behavior and Associated Factors Among High School Students in Gondar City, Northwest Ethiopia - Abebaw Wasie Kasahun; Mezgebu Yitayal; Tadele Girum; Bekri Mohammed (International Journal of Public Health Science (IJPHS), 2017)
According to World Health Organization (WHO), youth are young people within 15-24 years old. Studies reported that more than half of all new HIV infections occur among people between the ages of 15 and 24 years. Institution based quantitative cross-sectional study was conducted among high school students in Gondar city. Multistage sampling technique was employed to recruit study participants. Data were collected using pretested structured self-administered questionnaire. Data were entered in Epi Info version 7 and analyzed using SPSS version 21. Descriptive statistics were computed to describe important variables in relation to the outcome variable, Binary and multivariable logistic regressions were used to identify independent predictors of the outcome variable. The overall prevalence of risky sexual behavior was 12.8%. Two out of five sexually active respondents ever had unprotected sexual intercourse.  Ever used alcohol ((AOR, 3.53 95% CI (1.73-7.19)), had no parental monitor (AOR, 12.21 95% CI (6.55-22.78), ever watched pornographic film (AOR, 2.24 95% CI (1.15-4.35), had no parental discussion on sexual and reproductive health issues (AOR, 2.57 95% CI (1.36-4.85) and peer pressure (AOR,2.50, 95%CI (1.20-5.21), were factors which significantly increases the odds of risky sexual behavior among youth. Risky sexual behavior among high school students in Gondar city administration was very high and worrisome; so that collaborated effort is needed from parents, schools, health facilities and health policy makers to bring healthy sexual behavior among school youth.